Pengaruh Kegiatan Tambang Masyarakat Terhadap Lingkungan di Desa Parempei Kecamatan Rungan Kabupaten Gunung Mas Kalimantan Tengah - Azizah, Najwa; Safitri, Indri; Kukarnia, Septio; Kevin, Sebastian; Wijaya, Dody Ariyantho Kusma (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Gold mining carried out by local communities has a negative impact on environmental conditions, especially pollution in the Kahayan River basin. The purpose of this study was to describe the pollution control carried out by the government in the Rungan River basin which was polluted due to gold mining activities carried out by the community in Parempei Village, Central Kalimantan. The research method used in this study was the observation method. The use of mercury by local gold miners on a small scale is the main cause of pollution in the Rungan River basin, so that it exceeds the acceptable water quality standards. The findings of this study indicate that the efforts made by the government in overcoming pollution in the Rungan River basin are still lacking, which is also caused by several factors such as the lack of binding government affirmation regarding river pollution control, lack of public awareness in protecting the environment, and poor practices in imposing sanctions and law enforcement for miners.